The White Paper on a National Health Service (letter) - Trades Union Congress; Hartley, J. W.
1944-06-19 1944 1940s 2 pages cont. (2) (a) Contructive [Constructive] proposals that would recognise the value of the maintenance of voluntary hospitals contributory schemes in relation to a comprehensive health service. (b) A national propaganda campaign on the "White Paper" (c) A Speakers' Panel, for the purpose of publicising the story of the Voluntary Hospitals and Contributory Schemes in all parts of the country. (d) That every Voluntary Hospital, Contributory Scheme and member of the British Medical Association be asked to submit their suggestions and/or plans forthwith to the 'ad hoc' Committee. In view of these allegations the Chorley Division Trades Council passed the following resolution:- "That this meeting of the Chorley Division Trades Council believes that the best interests of the community will be served by the merging of Voluntary Hospitals within the Governments proposed National Health Service. It repudiates the statements which are being made by those people who are seeking to maintain the present system of financing Voluntary Hospitals through Contributory Schemes as representing the views of organised workers." I was directed to forward copies of the above resolution to the Trades Union Congress and the Lancashire & Cheshire Federation of Trades Councils, and to suggest that in view of the earnestness with which these two associations are displaying towards the White Paper, the T.U.C. should seriously consider issuing to all its affiliated Trades Councils a circular seeking local imformation [information] in this matter, and particularly in regard to those members of local contributory schemes and who may have representative on these bodies. On behalf of the above council, I am, yours faithfully, J.W. Hartley Hon. Corr. Secretary. 292/847/2/50